2013
DOI: 10.4103/2141-9248.122105
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and awareness regarding Hepatitis B and Hepatitis C amongst health-care workers of a tertiary Hospital in India

Abstract: Background:Hepatitis is an inflammatory disease of the liver. In sever cases, it may lead to permanent liver damage including liver cirrhosis or hepato-cellular carcinoma and may ultimately lead to death. Health-care workers (HCWs), due to their regular contact with patients are at a high-risk of acquiring this disease.Aim:The aim of this study was to assess the knowledge and attitude toward hepatitis B and C infection among the health-care interns and correlate the level of awareness to the attitude they beho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 21 publications
5
22
1
Order By: Relevance
“…Responders’ knowledge score in all domains were higher than among advanced educational level. Our results are in line with the findings from studies reported more educated worker related with more knowledge toward HBV and HCV [15, 23, 24]. Setia et al investigated awareness toward HBV and HCV amongst HCWs of a tertiary level hospital in India, indicated nursing students’ knowledge was considerably lower than the dental and medical students [24] As well as, a study in Turkey indicated that mean knowledge score was significantly higher in fourth-year students than third-year students [25].…”
Section: Discussionsupporting
confidence: 93%
“…Responders’ knowledge score in all domains were higher than among advanced educational level. Our results are in line with the findings from studies reported more educated worker related with more knowledge toward HBV and HCV [15, 23, 24]. Setia et al investigated awareness toward HBV and HCV amongst HCWs of a tertiary level hospital in India, indicated nursing students’ knowledge was considerably lower than the dental and medical students [24] As well as, a study in Turkey indicated that mean knowledge score was significantly higher in fourth-year students than third-year students [25].…”
Section: Discussionsupporting
confidence: 93%
“…This may be due to their lack of awareness regarding the various modes of transmission of HBV. If this misconception is not guarded against, it may lead to refusal of treatment and a decline in the quality of medical care provided [8]. In contrast, dental students (88.3%) showed more willingness towards treating patients with HBV.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare professionals are at an increased risk of acquiring blood-borne infectious diseases [6-8]. These individuals are prone to needle-stick injuries during procedures, leading to inadvertent inoculation of infected blood [2].…”
Section: Introductionmentioning
confidence: 99%
“…Khartoum State has seven localities within an area of 22.000 km 2 and approximately 6,430,000 inhabitants according to 2008 census of Sudan. The study populations were village midwives.…”
Section: Methodsmentioning
confidence: 99%
“…Almost all types of health care workers are at the risk of having Hepatitis B virus and they must acquire a higher level of knowledge for protection. Awareness about modes of transmission of Hepatitis B virus and vaccination is essential for universal precautions among the health care workers, where it was found that the knowledge is correlated positively with the behavior [2,3]. Globally, the attribute fractions of risk among health care workers to acquire blood borne diseases due to percutaneous injuries are 37% for Hepatitis B virus, 39% for Hepatitis C virus, and 4.4% for Human Immunodeficiency Virus [4].…”
Section: Introductionmentioning
confidence: 99%